Causal Relations Between Knowledge, Norms, and Tax: A Study of Gender Differences on Taxpayers - Irina Natasha; Andi Ina Yustina (Universitas Muhammadiyah Ponorogo, 2020)
This research analyzes whether tax knowledge and social norms positively influence tax compliance and whether gender differences will moderate their relation. A web-based survey used to spread questionnaires to 145 taxpayers that domiciled in Cikarang. The results revealed that tax knowledge significantly affects tax compliance, but there are no gender differences between tax knowledge and tax compliance. In contrast, social norms positively affect tax compliance, and gender differences also exist between social norms and tax compliance. As there are no gender differences in tax knowledge and tax compliance, socialization can be done with the same approach towards both males and females. However, gender differences in social norms lead to a difference between males and females in their point of view regarding tax. As most of the female internalized norms more than males, therefore a group with the majority of females more efficient in socialization. On the other hand, providing detail information and fact in socialization is more suitable for a male.